Manajemen Strategis dalam Peningkatan Publikasi Jurnal Ilmiah Internasional Bereputasi di Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Lampung - Irsyad Fadoli; Dodi Faedlulloh; Khairunnisa Simbolon; Vito Frasetya (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2024)
This study investigates the strategic management process employed by the Faculty of Social and Political Sciences (FISIP) at the University of Lampung to enhance the production of reputable international journal publications. In contemporary academia, publications in prestigious journals are of paramount importance, as they not only contribute to the expansion of knowledge within specific scientific fields but also significantly bolster the university's reputation at both national and international levels. This research adopts a qualitative methodology, utilizing interviews and observations to explore the perspectives and behaviors of participants. The study is further enriched by the analysis of secondary data sources, which provide essential contextual insights. Findings from this research indicate that the strategic management process has not been fully optimized, primarily due to challenges encountered during the initial phase, particularly in environmental scanning. Inadequacies in this phase have a cascading effect, undermining the overall effectiveness of the publication strategy. The theoretical implications underscore the critical role of thorough environmental scanning in strategic management. Comprehensive and detailed environmental analysis is indispensable for informed decision-making and strategic planning, especially for academic institutions striving for excellence in research publication.